Crime and mentalities in early modern England - Gaskill, Malcolm (Cambridge studies in early modern British history., 2000)
"Crime and Mentalities in Early Modern England attempts to reach further than most conventional treatments of the subject, to explore the cultural contexts of law-breaking and criminal prosecution, and to recover their hidden social meanings." "Conversely, the book exploits crime to shed light on the long-term development of English mentalities in general. To this end, three serious crimes - witchcraft, coining (counterfeiting and coin-clipping) and murder - are examined in detail, using a wide range of primary sources, revealing insights into how religious reform, state formation, secularisation, and social and cultural change (for example, the spread of literacy and the availability of print) may have transformed the thinking and outlook of most ordinary people between 1550 and 1750"--Jacket